Association between thyroid hormone levels and frailty in the community-dwelling oldest-old: a cross-sectional study. Issue 16 (20th August 2022) - Guan, Bo; Luo, Jiakun; Huang, Xin; Tian, Fan; Sun, Shasha; Ma, Yufei; Yu, Yan; Liu, Ruihan; Cao, Jian; Fan, Li
Abstract: Background: Changes in thyroid hormone levels are commonly recognized characters among the elderly, which were reported to potentially influence incident frailty. Therefore, we examined the cross-sectional associations of thyroid hormones (THs) with frailty as well as the five components characterizing frailty (fatigue, resistance, ambulation, number of illnesses, and loss of weight) among the oldest-old. Methods: Four hundred and eighty-seven community-dwelling oldest-old from a local community in Haidian District, Beijing, participated in our recruitment campaign between April 2019 and May 2020. The primary outcomes were a definitive diagnosis of frailty according to the FRAIL scale (Fatigue, Resistance, Ambulation, Illnesses, Loss of weight) and a positive score for each frailty subdomain. Demographic information (age, sex, marital status, and educational status), comorbidities, and details on the participants' lifestyles were recorded. Serum THs including free triiodothyronin (fT3), triiodothyronine (T3), free thyroxine (fT4), and thyroxine (T4) and thyroid stimulating hormone (TSH) levels were also measured at the beginning of our study. Logistic regressions were conducted to screen for potential risk factors for frailty and its subdomains. Results: Among the total 487 subjects at enrollment, 60 (12.23%) of them were diagnosed with subclinical hypothyroidism and 110 (22.59%) of the total population scored positive for frailty. Logistic regression analyses adjusted for all potential confounders, showed that frailty was significantly associated with the serum TSH concentration (odds ratio [OR]: 1.06), fT3 concentration (OR: 0.54), and subclinical hypothyroidism score (OR: 2.18). The association between fT4 and frailty was absent in our observational study. The fT3/fT4 ratio characterizing peripheral hormone conversion was also tested to be correlated with frailty. Conclusion: Subclinical hypothyroidism, higher TSH level, lower fT3 level, and decreased fT3/fT4 ratio were all associated with frailty assessed by the FRAIL scale among the community-dwelling oldest-old, suggesting a relevant role of thyroid function in aging. Future longitudinal studies are warranted to determine the casual relationship between thyroid dysfunction and frailty in the oldest-old.